Selective Incision of the α-N5-Methyl-Formamidopyrimidine Anomer by Escherichia coli Endonuclease IV. (30th June 2010) - Christov, Plamen P.; Banerjee, Surajit; Stone, Michael P.; Rizzo, Carmelo J.
Abstract : Formamidopyrimidines (Fapy) lesions result from ring opening of the imidazole portion of purines. Fapy lesions can isomerize from the naturalβ -anomeric stereochemistry to theα -configuration. We have unambiguously demonstrated that theα -methyl-Fapy-dG (MeFapy-dG) lesion is a substrate for Escherichia coli Endonuclease IV (Endo IV). Treatment of a MeFapy-dG-containing 24 mer duplex with Endo IV resulted in 36–40% incision. The catalytic efficiency of the incision was comparable to that ofα -dG in the same duplex sequence. Theα - andβ -MeFapy-dG anomers equilibrate to 21 : 79 ratio over 3 days. Related studies with a duplex containing theα -Fapy-dG lesion derived from aflatoxin B1 epoxide (α -AFB-Fapy-dG) showed only low levels of incision. It is hypothesized that the steric bulk of the aflatoxin moiety interferes with the binding of the substrate to Endo IV and the incision chemistry.